Hubungan Antara Perilaku Makan dan Healthy Eating Index dengan Status Gizi Anak Usia Sekolah di SDI Darush Sholihin Kabupaten Nganjuk - Yovicristy Latersia; Silvia Alfinnia Alfinnia; Lailatul Muniroh (Universitas Airlangga, 2022)
Background: School-age children are in the phase of growth and development so that nutrition intake is needed to support the growth and development of children. If there is an imbalance between intake and fulfillment of nutrition, nutritional problems will arise. Objectives: The study aims to analyze the relations between eating behavior and Healthy Eating Index with nutritional status of school-age children at SDI Darush Sholihin, Kabupaten Nganjuk. Methods: This research was an analytic observational with a cross-sectional design. The sample size were 48 students selected using proportional random sampling. The data collected includes weight, height, Food Frequency Questionnaire, and 2x24 hours food recall. The data was analyzed by Spearman correlation test with a significance value of 0.05. Results: Most students were male (54.2%), average energy intake 1126.08±287.99 kcal/day, low levels of intake such as carbohydrates (98%), protein (47.9%), and fat (64.6%), rare eat staple foods (60.4%), often eat plant proteins (43.8%), never eat vegetables (58.3%), fruits (81.2%), and snacks (75%). There was no correlation between eating behavior of staple foods (p=0.101), animal proteins (p=0.212), plant proteins (p=0.829), vegetables (p=0.751) and snacks (p=0.109), and Healthy Eating Index score (p=0.194) with nutritional status. However, fruit eating behavior (p=0.040) was associated with nutritional status. Conclusions: There was no positive correlation between eating behavior of staple foods, animal proteins, plant proteins, vegetables, and snacks, and also HEI score with nutritional status. However, there was a correlation between fruit eating behavior with nutritional status. Children who often eat fruit without paying attention to the sugar content and serving method are at risk of becoming obese. Nutrition education to schools and parents related to healthy eating behavior, especially fruit, is needed to prevent obesity and achieve optimal growth and development.